3D Hetero-architecture of GdB6 nanoparticles on lessened cubic Cu2O nanowires: enhanced field emission behaviour - Suryawanshi, Sachin R.; Singh, Anil K.; Deo, Meenal S.; Late, Dattatray J.; Sinha, Sucharita; More, Mahendra A. (CrystEngComm, 2015)
The field emission properties (FE) of a heteroarchitecture comprised of gadolinium hexaboride nanoparticles uniformly decorated over Cu2O nanoneedles (GdB6/Cu2O) have been investigated at the base pressure of similar to 1 x 10(-8) mbar. Under the optimized pulsed laser deposition (PLD), a well-adhered coating of GdB6 nanoparticles on chemically synthesized cuprous oxide (Cu2O) nanoneedles has been obtained. A plausible growth mechanism of the hierarchical assembly of GdB6 nanoparticles on the Cu2O nanoneedles is explained on the basis of structural analysis carried out using SEM and TEM. A low turn-on field of similar to 2.3 V mu m(-1) (to draw an emission current density similar to 1 mu A cm(-2)) is observed along with stable emission current at the preset value of similar to 2 mu A over 4 h. The enhanced emission behaviour of the GdB6/Cu2O heteroarchitecture, in contrast to the pristine Cu2O nanoneedles, is attributed to its high aspect ratio and low work function. The observed FE results demonstrate GdB6/Cu2O heteroarchitecture as a potential candidate for application in various vacuum nano/microelectronic devices.

Facile approach towards fabrication of GdB6-ZnO heteroarchitecture as high currentdensity cold cathode - Suryawanshi, Sachin R.; Mistari, Chetan D.; Singh, Anil K.; Phase, Deodatta M.; Late, Dattatray J.; Sinha, Sucharita; More, Mahendra A. (Chemistryselect, 2016)
Three dimensional (3D) GdB6-ZnO heteroarchitecture comprised of thin coating of GdB6 on self aligned ZnO urchins with pointed apex has been synthesized employing optimized Pulsed Laser Deposition (PLD) technique. The self aligned ZnO urchins on Zn substrate were obtained using hydrothermal route. The as-synthesized GdB6-ZnO heteroarchitecture was characterized using XRD, SEM, TEM XPS, and UPS in order to reveal its structural, morphological, chemical, and electronic properties. Interestingly, the GdB6-ZnO heteroarchitecture exhibits superior field emission (FE) behviour in contrast to the pristine ZnO urchins envisaged by extraction of very high emission current density of similar to 4.6 mA/cm(2) at an applied field of similar to 4.5 V/mm, against similar to 1.5 mA/cm(2) at an applied field of similar to 5.6 V/mm from the pristine ZnO urchins emitter. Furthermore, the GdB6-ZnOemitter exhibits good emission stability at pre-set value of similar to 5 mA over duration of more than 3 hours. The superior FE behaviour of the GdB6-ZnO is attributed to low work-function of GdB6 and presence of nanometric protrusions on the emitter surface, further enhancing the aspect ratio provided by the ZnO urchins. The present results demonstrate a facile approach towards fabrication of high current density cold cathodes due to rare earth hexaborides via designing hetero-architectures comprised of their well adherent ultrathin coating on high aspect ratio metal oxide nanostructures.

Pulsed laser-deposited nanocrystalline GdB6 thin films on W and Re as field emitters - Suryawanshi, Sachin R.; Singh, Anil K.; Phase, Deodatta M.; Late, Dattatray J.; Sinha, Sucharita; More, Mahendra A. (Applied Physics A-Materials Science & Processing, 2016)
Gadolinium hexaboride (GdB6) nanocrystalline thin films were grown on tungsten (W), rhenium (Re) tips and foil substrates using optimized pulsed laser deposition (PLD) technique. The X-ray diffraction analysis reveals formation of pure, crystalline cubic phase of GdB6 on W and Re substrates, under the prevailing PLD conditions. The field emission (FE) studies of GdB6/W and GdB6/Re emitters were performed in a planar diode configuration at the base pressure similar to 10(-8) mbar. The GdB6/W and GdB6/Re tip emitters deliver high emission current densities of similar to 1.4 and 0.811 mA/cm(2) at an applied field of similar to 6.0 and 7.0 V/mu m, respectively. The Fowler-Nordheim (F-N) plots were found to be nearly linear showing metallic nature of the emitters. The noticeably high values of field enhancement factor (beta) estimated using the slopes of the F-N plots indicate that the PLD GdB6 coating on Wand Re substrates comprises of high-aspect-ratio nanostructures. Interestingly, the GdB6/W and GdB6/Re planar emitters exhibit excellent current stability at the preset values over a long-term operation, as compared to the tip emitters. Furthermore, the values of workfunction of the GdB6/W and GdB6/Re emitters, experimentally measured using ultraviolet photoelectron spectroscopy, are found to be same, similar to 1.6 +/- 0.1 eV. Despite possessing same workfunction value, the FE characteristics of the GdB6/W emitter are markedly different from that of GdB6/Re emitter, which can be attributed to the growth of GdB6 films on W and Re substrates.